Recent Advances on Magnetic Sensitive Hydrogels in Tissue Engineering - Liu, Zhongyang; Liu, Jianheng; Cui, Xiang; Wang, Xing; Zhang, Licheng; Tang, Peifu (Frontiers in Chemistry, 2020)
Tissue engineering is a promising strategy for the repair and regeneration of damaged tissues or organs. Biomaterials are one of the most important components in tissue engineering. Recently, magnetic hydrogels which are fabricated using by iron oxide-based particles and different types of hydrogel matrices are becoming more and more attractive in biomedical applications by taking advantage of their biocompatibility, controlled architectures, and smart response to magnetic field remotely. In this literature review, the aim is to summarize the current development of magnetically-sensitive smart hydrogels in tissue engineering, which is of great importance but has not yet been comprehensively viewed.